2021
DOI: 10.1002/arco.5223
|View full text |Cite
|
Sign up to set email alerts
|

The stone adze and obsidian assemblage from the Talasiu site, Kingdom of Tonga

Abstract: Typological and geochemical analyses of stone adzes and other stone tools have played a significant role in identifying directionality of colonisation movements in early migratory events in the Western Pacific. In later phases of Polynesian prehistory, stone adzes are important status goods which show substantial spatial and temporal variation. However, there is a debate when standardisation of form and manufacture appeared, whether it can be seen in earliest populations colonising the Pacific or whether it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Adzes are not common in Lapita archaeological sites, but a site in Tonga dating from 2700-2500ya, a relatively early phase in the settlement of Western Polynesia, yielded a variety of complete and fragmentary stone adzes. These adzes were mainly plano-convex forms lacking obvious tangs (Reepmeyer et al 2021). The assemblage is not obviously different from blades found in New Guinea (for example), implying that distinctive Polynesian forms developed after this primary colonization event.…”
Section: Polynesiamentioning
confidence: 64%
“…Adzes are not common in Lapita archaeological sites, but a site in Tonga dating from 2700-2500ya, a relatively early phase in the settlement of Western Polynesia, yielded a variety of complete and fragmentary stone adzes. These adzes were mainly plano-convex forms lacking obvious tangs (Reepmeyer et al 2021). The assemblage is not obviously different from blades found in New Guinea (for example), implying that distinctive Polynesian forms developed after this primary colonization event.…”
Section: Polynesiamentioning
confidence: 64%
“…Adzes are not common in Lapita archaeological sites, but a site in Tonga dating from 2700-2500ya, a phase that followed on from the initial settlement of Western Polynesia, yielded a variety of complete and fragmentary stone adzes. These adzes were mainly forms with lenticular and planoconvex cross-sections, lacking tangs (Reepmeyer et al 2021). The assemblage is not obviously different from blades found in New Guinea, 6 and the authors note that evidence for a distinctive 'Lapita adze kit' is scarce.…”
Section: Polynesiamentioning
confidence: 80%
“…I have reexamined these closely with one determined to be a nonvolcanic material and another with a context wrongly grouped with Lapita. Reepmeyer et al (2021) have more recently identified a small number of Sāmoan adze flakes/fragments in late Lapita deposits at Talasiu. premise.…”
Section: The Polynesian Plainware Phase In Tongan Archaeologymentioning
confidence: 99%